(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Teacher self-efficacy, the belief in one’s ability to effectively teach and facilitate student learning, is a critical factor influencing pedagogical practices and student outcomes. Social media platforms, with their diverse functionalities and global reach, offer numerous opportunities for teachers to connect with peers, access professional development resources, and engage in collaborative learning communities. By fostering a sense of belonging and providing a platform for knowledge sharing, social media can positively impact teacher self-efficacy. Social media has emerged as a powerful tool that has the potential to revolutionize the way educators learn and teach. This research aims to bridge this gap by examining the relationship between social media usage and teacher educators’ perceived self-efficacy. By investigating the extent to which teacher educators utilize social media platforms and how these platforms influence their beliefs in their teaching abilities, this study contributes to a better understanding of the role of technology in professional development.